Epigenetic Changes in Neonates Born to Mothers With Gestational Diabetes Mellitus May Be Associated With Neonatal Hypoglycaemia - Kasuga, Yoshifumi; Kawai, Tomoko; Miyakoshi, Kei; Saisho, Yoshifumi; Tamagawa, Masumi; Hasegawa, Keita; Ikenoue, Satoru; Ochiai, Daigo; Hida, Mariko; Tanaka, Mamoru; Hata, Kenichiro (Frontiers in Endocrinology, 2021)
The detection of epigenetic changes associated with neonatal hypoglycaemia may reveal the pathophysiology and predict the onset of future diseases in offspring. We hypothesized that neonatal hypoglycaemia reflects the in utero environment associated with maternal gestational diabetes mellitus. The aim of this study was to identify epigenetic changes associated with neonatal hypoglycaemia. The association between DNA methylation using Infinium HumanMethylation EPIC BeadChip and neonatal plasma glucose (PG) level at 1 h after birth in 128 offspring born at term to mothers with well-controlled gestational diabetes mellitus was investigated by robust linear regression analysis. Cord blood DNA methylation at 12 CpG sites was significantly associated with PG at 1 h after birth after adding infant sex, delivery method, gestational day, and blood cell compositions as covariates to the regression model. DNA methylation at two CpG sites near an alternative transcription start site of ZNF696 was significantly associated with the PG level at 1 h following birth (false discovery rate-adjusted P < 0.05). Methylation levels at these sites increased as neonatal PG levels at 1 h after birth decreased. In conclusion, gestational diabetes mellitus is associated with DNA methylation changes at the alternative transcription start site of ZNF696 in cord blood cells. This is the first report of DNA methylation changes associated with neonatal PG at 1 h after birth.